2016
DOI: 10.1016/j.jtbi.2015.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dispersal on the stability of metapopulations

Abstract: Dispersal is a key ecological process that enables local populations to form spatially extended systems called metapopulations. In the present study, we investigate how dispersal affects the linear stability of a general single-species metapopulation model. We discuss both the influence of local within-patch dynamics and the effects of various dispersal behaviours on stability. We find that positive density-dependent dispersal and positive density-dependent settlement are destabilizing dispersal behaviours whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 69 publications
(126 reference statements)
1
17
0
Order By: Relevance
“…Finally, superlinear mortality rates, such as quadratic mortality, have a stabilizing effect that can be much stronger than the effect of dispersal, thus that dispersal does not generally lead to a destabilization of such systems. These findings are consistent with Tromeur et al (2013), who studied the dynamics of a single population in a system with many patches. In contrast to this previous study we found that dispersal can in certain cases be stabilizing in the two-species system.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Finally, superlinear mortality rates, such as quadratic mortality, have a stabilizing effect that can be much stronger than the effect of dispersal, thus that dispersal does not generally lead to a destabilization of such systems. These findings are consistent with Tromeur et al (2013), who studied the dynamics of a single population in a system with many patches. In contrast to this previous study we found that dispersal can in certain cases be stabilizing in the two-species system.…”
Section: Discussionsupporting
confidence: 91%
“…In ecology both the exploration of dynamical models of food webs (Pascual and Dunne, 2005;Thompson et al, 2012;Rooney and McCann, 2012) and the study of spatial metapopulations (Holland and Hastings, 2008;Hanski and Gaggiotti, 2004;Tromeur et al, 2013) are well established lines of research. The two modelling approaches emphasize different aspects of ecological dynamics that are both relevant for most species: the dispersal between different habitat patches and tropic interactions with other species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon can occur when selection forces are tied to such sudden environmental effects as algal blooms or flooding [1], or it can arise from more subtle, population-level effects such as overcrowding or resource depletion [2]. Analysis of such interactions within a unified theory of “eco-evolutionary dynamics” has been applied to a wide range of systems—from bacteria-phage interactions to bighorn sheep [3]—by describing population fluctuations in terms of the feedback between demographic change and natural selection [4].…”
Section: Introductionmentioning
confidence: 99%
“…The second avenue of investigation asks how spatial distribution affects the persistence of species. Early models considered only a single species in space, a socalled meta-populations [29][30][31]. These models were subsequently extended to meta-communities, systems of competing similar species, e.g.…”
Section: Introductionmentioning
confidence: 99%